2017
DOI: 10.1111/iere.12231
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomy of U.S. Personal Bankruptcy Under Chapter 13

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Chapter 13 filers may be at a disadvantage given their substantial recidivism in delinquency. As shown in Norberg and Velkey (2007) and Eraslan et al (2014), only 33% of all Chapter 13 filers successfully complete the court mandated repayment plan. Moreover, 30-33% of Chapter 13 filers whose bankruptcy was discharged or dismissed filed again at least once.…”
Section: Insolvency Bankruptcy and Access To Creditmentioning
confidence: 98%
“…Chapter 13 filers may be at a disadvantage given their substantial recidivism in delinquency. As shown in Norberg and Velkey (2007) and Eraslan et al (2014), only 33% of all Chapter 13 filers successfully complete the court mandated repayment plan. Moreover, 30-33% of Chapter 13 filers whose bankruptcy was discharged or dismissed filed again at least once.…”
Section: Insolvency Bankruptcy and Access To Creditmentioning
confidence: 98%
“…First, Chapter 7 bankruptcy is the form of bankruptcy that offers the most effective form of debt relief, when the bankruptcy is discharged, and comprises the largest fraction of bankruptcy procedures, both pre-and post reform. As shown in Norberg and Velkey (2007) and Eraslan et al (2014), only 33% of all Chapter 13 bankruptcies are discharged, which corresponds to the fraction of filers that successfully complete the court mandated repayment plan. 2002 2003 2006 2007 2008 2009 2010 2011 2012--1 4 2002 2003 2006 2007 2008 2009 2010 2011 2012 Figure 3: β s(t) for 4 quarter ahead transition probability from Newly Delinquent (left panel) and Newly Insolvent (right panel) to Chapter 13 bankruptcy filings.…”
Section: The Effects Of Bapca Over Timementioning
confidence: 99%
“…Eraslan et al. () found that that completion of repayment plans depends heavily on the debtors’ circumstances following filing. Shocks to income from unemployment and family disruption are significant predictors of whether a repayment plan is completed (Elul and Gottardi, ).…”
Section: Conceptual Model Of Financial Well‐beingmentioning
confidence: 99%